Protocol of GIOP onto RapidIO——RIO-IOP - Wen-yu CHEN; Ru ZENG; Wei PI; Wen LI (Tongxin xuebao)
In embedded system application,all hardware elements based on bus mode.TCP/IP can not satisfy their communications,especially the interconnection of chips and boards.Therefore,in embedded environment,RapidIO interconnection framework is employed.There is not the mapping of GIOP onto RapidIO.This paper taked example by IIOP,and proposed the mapping of GIOP onto RapidIO:RIO-IOP.It analyzed RIO-IOP from the network model and the transport component model aspects in an all-round.RIO-IOP also supported the basic service of CORBA.In embedded field and military environment in the hardware,there is obvious advantages and application prospect by RIO-IOP experimentation.